Ultrasound Joint Inflammation in Rheumatoid Arthritis in Clinical Remission: How Many and Which Joints Should Be Assessed?. Issue 4 (28th March 2013) - Naredo, Esperanza; Valor, Lara; De la Torre, Inmaculada; Martínez‐Barrio, Julia; Hinojosa, Michelle; Aramburu, Francisco; Ovalles‐Bonilla, Juan Gabriel; Hernández, Diana; Montoro, María; González, Carlos Manuel; López‐Longo, Javier; Monteagudo, Indalecio; et al.
Abstract Objective To investigate the sensitivity for detecting subclinical synovitis of different reduced joint ultrasound (US) assessment models as compared with a comprehensive US assessment in rheumatoid arthritis (RA) patients in clinical remission. Methods Sixty‐seven RA patients (50 women, 17 men) in clinical remission as judged by their consultant rheumatologist and treated with methotrexate were prospectively recruited. Patients were evaluated for disease activity according to the Disease Activity Score in 28 joints (DAS28) and the Simplified Disease Activity Index (SDAI) by the same investigator. Each patient underwent a 44‐joint B‐mode and power Doppler (PD) assessment by a rheumatologist blinded to the clinical and laboratory data. B‐mode synovial hypertrophy (SH) and synovial PD signal were scored from 0–3 at each joint. Global indices for SH and PD signal were calculated for the 44‐joint and different joint combination models for each patient. Results SH was detected in 87.8% of patients with a DAS28 <2.6 and in 81.8% of patients with an SDAI <3.3. Synovial PD signal was detected in 46.3% of patients with a DAS28 <2.6 and in 36.4% of patients with an SDAI <3.3. Wrist, second through fifth metacarpophalangeal (MCP), ankle, and second through fifth metatarsophalangeal (MTP) joint and 12‐joint US assessments showed the highest correlations with the comprehensive US assessment. The wrist, MCP, ankle, and MTP joint US assessment showed the highest sensitivity for detecting SH and synovial PD signal in patients in remission according to the DAS28 and SDAI as compared to the comprehensive US assessment. Conclusion US assessment of the wrist, MCP, ankle, and MTP joints can be highly sensitive for detecting residual B‐mode and Doppler joint inflammation in RA patients.